Pengaruh Disiplin terhadap Kinerja Pegawai Bagian Umum pada Sekretariat Daerah Muaro Jambi - Lidia Lidia (Universitas Batanghari Jambi, 2019)
fistly, this research to analyse how toto know how implementation of discipline and employee performance in the general section at District Secretariat Muaro Jambi.How the effect of dicipline on employee performance at general section at District Secretariat Muaro Jambi.The research methodology is descriptive and quantitative analysis methods. Data used is primary data.The sample have 35 respondents. Method for analysis is analysis simply regression, hypotesis test, correlation so determinant coefficient and t_test.Analysis on the research of respondents felt a discipline in the performance of tasks provided by the superiors. The highest score ini dicsiplined variable is to abey the orders of the employer of 145 score is high category. Simple linear regression equations are Y = 7.852 + 0.286X + E. Where the reseach result, discipline has a significant effect on employee performance, calculation result of tcount is greater than ttable. Conclusion that the discipline has significant effect on performance and have a positive relationship in the general section at District Secretariat Muaro Jambi.Chief of General section of the Muaro Jambi Regional secretariat needs to maintain existing policies and need to make new breakthroughs to improve employee work productivity e.g. in variable compensation or variable design Career.